Evaluation of synergistic effect of entomopathogenic fungi Beauveria bassiana and Lecanicillium lecacii on the mosquito Culex quinquefaciatus. - Aditya Shankar Kataki; Francesco Baldini; Anjana Singha Naorem (PLoS ONE)
Vector-borne diseases resulted into several cases of human morbidity and mortality over the years and among them is filariasis, caused by the mosquito Culex quinquefasciatus. Developing novel strategies for mosquito control without jeopardizing the environmental conditions has always been a topic of discussion and research. Integrated Vector Management (IVM) emphasizes a comprehensive approach and use of a range of strategies for vector control. Recent research evaluated the use of two entomopathogenic fungi; Beauveria bassiana and Lecanicillium lecanii in IVM, which can serve as potential organic insecticide for mosquito population control. However, their combined efficacy has not yet been evaluated against mosquito control in prior research and a gap of knowledge is still existing. So, this research was an attempt to bridge up the knowledge gap by (1) Assessing the combined efficacy of Beauveria bassiana and Lecanicillium lecanii on Culex quinquefasciatus (2) To investigate the sub-lethal concentration (LC50) of the combined fungal concentration and (3) To examine the post-mortem effects caused by the combined fungal concentration under Scanning Electron Microscope (SEM). The larval pathogenicity assay was performed on 4th instar C. quinquefasciatus larvae. Individual processed fungal solution of B. bassiana and L. lecanii were procured and to test the combined efficacy, the two solutions were mixed in equal proportions. To evaluate the sub-lethal concentration (LC50), different concentrations of the combined fungal solution were prepared by serial dilations. The mortality was recorded after 24 hours for each concentration. Upon treatment and evaluation, The LC50 values of B. bassiana and L. lecanii were 0.25 x 104 spores/ml and 0.12 x 104 spores/ml respectively and the combined fungal concentration was 0.06 x 103 spores/ml. This clearly indicated that the combined efficacy of the fungi is more significant. Further, SEM analysis revealed morphological deformities and extensive body perforations upon combined fungal treatment. These findings suggested that combining the two fungi can be a more effective way in controlling the population of Culex quinquefasciatus.